(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the artistic embodiment of the humanist idea in Charles Dickens’s Dombey and Son (1846–1848), a novel that marks the beginning of the writer’s mature period. It argues that, in contrast to the early fiction, where humanist values are conveyed through the direct opposition of virtue and vice, Dombey and Son realizes those values through a complex artistic system in which the architectonics of the characters, the symbolic richness of space, and the psychological transformation of the protagonist work together. The study focuses on three structural carriers of the humanist idea: the critique of commercial values embodied in Mr Dombey and in the marriage of Edith Granger; the symbolic opposition of the cold house and the sea; and the poetics of moral awakening in the novel’s resolution. The analysis employs close reading and structural-semantic methods. The findings indicate that Dickens affirms human dignity against the background of a triumphant bourgeois mercantilism, and that the protagonist’s much-debated final transformation is artistically coherent when read not as psychological evolution but as moral awakening. The study contributes to an understanding of how the Victorian social novel asserted the value of the person in an age dominated by the logic of the market.